China's Economy and the Global Financial Crisis - Siami-Namini, Sima (International Journal of Economics and Financial Issues, 2017)
The aim of this article is to provide a brief overview of the increasing importance of China's economy around the world economy, and to discuss the impacts of the global financial crisis on China's economy. While China's economic growth remained well above international averages, its drop was of the same order of magnitude as for the US. The question is that how China responds to the global financial crisis. Using two individual vector auto-regression (VAR) models, I analyze the relationship between China's output and two foreign outputs including US and Germany over the period of 1979-2013. The results of VAR Granger-casualty show that China's output and US output does affect each other. Also, China's output affect Germany output, but not vice versa. Besides that, China's output illustrates variance decomposition (VDC) of US output with 3.21%, and US output explains VDC of China's output with 0.14%. China's output illustrates VDC of Germany output with 7.84%, and Germany output explains VDC of China's output with 1.36%. Therefore, the impact of US output shock on China is greater than Germany output shock. Keywords: Global Financial Crisis, China's Economy, Vector Auto-regression model (VAR). JEL Classifications: G01, E37, C32, F43.